Effect of exogenous p51a gene on the growth and chemo sensitivity of human lung adenocarcinoma cell lines. (12th November 2018) - Shen, Qiming; Wang, Haoyou; Zhang, Lin
Abstract: Background: The dysfunction of p53-mediated apoptosis is the key to tumorigenesis, so most gene therapy programs concentrate on improving the expressing level of wild-type p53 in tumour cells. However, the p53 gene therapy has not yielded satisfactory results in tumours with normal p53 function. A new member of p53 gene family-p63, has provided new hopes. TAp63γ (p51A) resembles p53 the most, thus it might become a new promising therapeutic gene of tumours. Methods: We designed the primer pairs of p51A and amplified the p51A cDNA sequence from human skeletal muscle poly A + RNA to construct recombinant plasmid. It was then transfected into human lung adenocarcinoma cell lines A549 and NCI-H1299. RT-PCR, Western blot, MTT, flow cytometry and colony formation assay were used to analyse the growth and chemosensitivity of tumour cells. Results: The recombinant plasmid was constructed and transfected into tumour cells successfully. After transfection, p51A mRNA, P51A protein and P21 protein level raised significantly. Cell proliferation capacity and colony formation rate decreased while cell apoptosis rate and chemosensitivity to cisplatin and adriamycin increased significantly. Conclusions: Exogenous p51A gene can increase its expression in A549 and NCI-H1299 cells, suppress cell growth and induce cell apoptosis. Moreover, it can also cooperate with chemotherapy and reduce the dose and side-effect. p51A gene can suppress tumours in spite of p53 status and p21 gene might be involved. It might become a new promising therapeutic gene of tumours, which will make up for the limitation of p53 gene therapy.